Distance education in the field of obstetrics, gynaecology, and ultrasound diagnostics in the conditions of quarantine restrictions and hostilities: A literature review - I. Sokolovska; S. Nakonechniy; I. Ganzhiy (Mukachevo State University, 2024)
Forced distancing in the context of the COVID-19 pandemic has necessitated the transition of medical education to distance learning. The problem was exacerbated by the outbreak of full-scale hostilities, which necessitated further research in this area. The purpose of the study was to comprehensively review current scientific materials and consolidate existing knowledge on educational activities in obstetrics, gynaecology, and ultrasound diagnostics in the context of the coronavirus pandemic and full-scale hostilities. The following methods were used for the study: bibliographic, analysis, synthesis, induction, generalization, analogy, systematization, and categorization. The article presents a comprehensive analysis of the current literature on overcoming pedagogical challenges in the context of the COVID-19 pandemic and military operations through the achievements of distance education. The methodological foundations of distance education, the peculiarities of applying this practice in a pandemic and military operations, the similarities, and differences between them, especially in the context of obstetrics, gynaecology and ultrasound diagnostics, are considered. The connection between telemedicine and distance learning is presented both at the level of theory and practice. The practice of distance learning in obstetrics and gynaecology is compared with some other clinical disciplines. The result of the study was to solve the problem of the lack of a systematic view of the adaptation of the educational process to the conditions of a pandemic and military operations as emergency distance learning, rather than the classical practice of distance education, which contributes to the formation of an adequate assessment of pedagogical activities conducted in such conditions, in particular, in the field of obstetrics, gynaecology, and ultrasound diagnostics. The results of the study are of practical importance in the field of medical education, where they can be used to develop recommendations for the organization of training in obstetrics and gynaecology or other medical disciplines in conditions of forced distance learning